Peran Intervening Kepuasan Kerja pada Pengaruh Disiplin Kerja dan Pengembangan Karir terhadap Kinerja Pegawai pada Fakultas Ekonomi dan Bisnis Universitas Sultan Ageng Tirtayasa - Siti Epa Hardiyanti (Tirtayasa Ekonomika, 2020)
A research aims to determine the effect of work discipline and career development on employee performance with a job satisfaction as an intervening variable at the Faculty of Economics and Business University of Sultan Ageng Tirtayasa. The sample using in the research as many as 40 respondents taken by direct observation and distribute a questionnaire on the employees at the Faculty of Economics and Business University of Sultan Ageng Tirtayasa. The method of analysis used in the research is path analysis (path analysis) by testing of t- statistics. The analyzer uses Smart-PLS Version 20. The results showed the discipline has an effect on employee performance because of the statistical t value (4,286 > 1,96) and p values (0,000 > 0,05). Discipline has no effect on job satisfaction because of statistical t value (0,959 <1,96) and p values (0,344> 0,05). Career development has an effect on job satisfaction because t value of statistic (2,822)> 1,96) and p value has a value of 0,008 < 0,05. Career development has an effect on employee performance because t value of statistic has a value 4,286 > 1,96, and p values 0,000 < 0,05. Satisfaction has no effect on the employee performance because the value of t statistic (1,272<1,96), also p value (0,211 > 0,05).